X linked- ALD: Should Loes score be the only benchmark for HSCT eligibility? HSCT in X linked ALD with high Loes score - Gupta, Aditya Kumar; Singh, Pavit; KN, Parvathy; Kumar, Atin; Das, Gargi; Chowdhury, Sayoni Roy; Meena, Jagdish Prasad; Chakrabarthy, Biswaroop; Jauhari, Prashant; Seth, Rachna; Gulati, Sheffali (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2025)
Hematopoietic stem cell transplant(HSCT) is the only modality that, if performed in the early- stages of cerebral X-linked adrenoleukodystrophy(X-ALD) can lead to good outcomes. Loes- score, calculated based on the findings of the magnetic resonance imaging(MRI) of the brain, helps in the selection of patients for HSCT. As per recommendations, the Loes-score should be <10 for a patient to be eligible for HSCT. Here we report a child of cerebral X-ALD with Loes of 12, but a good neurological function score(NFS), who was treated with HSCT, and had good outcomes. It is therefore important to utilize other parameters along with the Loes score, in selecting patients for HSCT in X-ALD.